2008
DOI: 10.1172/jci33869
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase–associated lipocalin mediates 13-cis retinoic acid–induced apoptosis of human sebaceous gland cells

Abstract: 13-cis retinoic acid (13-cis RA; also known as isotretinoin) is the most potent agent available for treatment of acne. It is known that the drug induces apoptosis in cells cultured from human sebaceous glands, but its mechanism of action has not been determined. In this study, skin biopsies were taken from 7 patients with acne prior to and at 1 week of treatment with 13-cis RA. TUNEL staining confirmed that 13-cis RA induced apoptosis in sebaceous glands. Transcriptional profiling of patient skin and cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
142
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 64 publications
6
142
0
2
Order By: Relevance
“…Detailed studies of NGAL's localization and function within the sebaceous gland demonstrated that NGAL mediates the apoptotic action of 13-cis RA on sebaceous glands, thereby suggesting that agents which selectively induce NGAL expression in sebaceous glands might represent therapeutic alternatives to the use of 13-cis RA for the treatment of acne. 1 In addition to NGAL, 13-cis RA affected the expression of numerous other genes in patient skin at one-week and in our sebocyte cell culture model, SEB-1. The results of these gene expression array analyses have been submitted to the National Center for Biotechnology Information Gene Expression Omnibus Database and are available under series accession number GSE10434.…”
mentioning
confidence: 82%
“…Detailed studies of NGAL's localization and function within the sebaceous gland demonstrated that NGAL mediates the apoptotic action of 13-cis RA on sebaceous glands, thereby suggesting that agents which selectively induce NGAL expression in sebaceous glands might represent therapeutic alternatives to the use of 13-cis RA for the treatment of acne. 1 In addition to NGAL, 13-cis RA affected the expression of numerous other genes in patient skin at one-week and in our sebocyte cell culture model, SEB-1. The results of these gene expression array analyses have been submitted to the National Center for Biotechnology Information Gene Expression Omnibus Database and are available under series accession number GSE10434.…”
mentioning
confidence: 82%
“…1B and C). 1 Significant decreases in expression of genes that regulate lipid metabolism were noted after 8 weeks of isotretinoin therapy. Gene array expression analysis was performed on patient skin biopsies at baseline and at 8 weeks of isotretinoin therapy in order to gain insight into putative pathways affected by 13-cis RA treatment.…”
Section: Patient Selectionmentioning
confidence: 99%
“…These data were compared to results from the array analysis and histology of skin from patients treated for one week as has recently been reported. 1 Distinctly different patterns of gene expression were noted depending upon the duration of therapy. In particular, marked decreases in the expression of genes involved in lipid metabolism were found at 8 weeks, which is in agreement with the marked decrease in sebaceous gland size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…lcn2 is also known as 24p3 and neutrophil gelatinase-associated lipocalin (NGAL) (Borregaard and Cowland, 2006). In vitro studies have shown that lcn2 is important for both cellular apoptosis and survival (Devireddy et al, 2001(Devireddy et al, , 2005Yousefi and Simon, 2002;Tong et al, 2003Tong et al, , 2005Nelson et al, 2008). It also plays an important role in the induction of cellular differentiation in kidney during embryogenesis (Yang et al, 2002) and protects the kidney from ischemic injury (Mishra et al, 2004;Mori et al, 2005).…”
Section: Introductionmentioning
confidence: 99%